DEVELOPMENT OF KNOWLEDGE OF STUDENTS THROUGH INDEPENDENT STUDY ON THE BASIS OF A SYSTEMATIC APPROACH (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Based on a systematic approach to music, this article allows students to learn independently and develop their personal knowledge, such as a guided learning plan.